Blitz : the club that created the 80s - Elms, Robert, 1959- (Faber & Faber, 2025)
The short-lived Blitz club in London's Covent Garden was more than somewhere to hang out or be seen: it was a catalyst for cultural explosion, a counter-culture blast against everything Thatcher's leadership had ushered in by the dawn of the 80s. Tuesday nights boasted a ferocious, fearless cast - from Boy George and Spandau Ballet to Grayson Perry and Peter Doig, to Michele Clapton, Sade and Alexander McQueen. This was the vanguard of a different England; socially liberal, loud, proud and diverse, fiercely individualistic and determined to succeed. Britain was black and white; the Blitz Kids switched on the colour. In this book, Elms reflects on a club night founded by working-class kids, one whose impact reverberated beyond its doors, through the worlds of Art, Literature, Fashion and Music, and into the present day.